2019
DOI: 10.1021/acschemneuro.9b00539
|View full text |Cite
|
Sign up to set email alerts
|

Liproxstatin-1 Attenuates Morphine Tolerance through Inhibiting Spinal Ferroptosis-like Cell Death

Abstract: Morphine tolerance is a classic, challenging clinical issue. However, the mechanism underlying this phenomenon remains poorly understood. Recently, studies have shown that ferroptosis correlates with drug resistance. Therefore, this study investigated whether spinal cord ferroptosis contributes to morphine tolerance. C57BL/6 mice were continuously subcutaneously injected with morphine, with or without the ferroptosis inhibitor liproxstatin-1. We found that chronic morphine exposure led to morphine antinocicept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…Ferroptosis is an iron‐dependent oxidative cell death (Tang et al, 2019), and is characterized by iron‐dependent reactive oxygen species (ROS) accumulation and inactivation of cellular antioxidant glutathione (GSH) (Sui et al, 2018). This type of cell death (ferroptosis) is genetically, biochemically and morphologically distinct from apoptosis (Chen et al, 2019; Tang et al, 2019). Recent studies have investigated the involvement of pyroptotic cell death in cancer development (Belavgeni et al, 2019; Carbone & Melino, 2019), and found that RSL3‐induced cell ferroptosis was relevant to CRC progression (Sui et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is an iron‐dependent oxidative cell death (Tang et al, 2019), and is characterized by iron‐dependent reactive oxygen species (ROS) accumulation and inactivation of cellular antioxidant glutathione (GSH) (Sui et al, 2018). This type of cell death (ferroptosis) is genetically, biochemically and morphologically distinct from apoptosis (Chen et al, 2019; Tang et al, 2019). Recent studies have investigated the involvement of pyroptotic cell death in cancer development (Belavgeni et al, 2019; Carbone & Melino, 2019), and found that RSL3‐induced cell ferroptosis was relevant to CRC progression (Sui et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The bona fide ferroptosis inhibitors ferrostatin-1 (Dixon et al, 2012) and liproxstatin-1 (Friedmann Angeli et al, 2014) exert their function as efficient radical trapping antioxidants (RTA), thereby preventing cellular autoxidation (Zilka et al, 2017). The protective effects of these compounds in mouse disease models include ischemia/reperfusion injuries of the kidney, liver, brain, heart, and intestine (Fang et al, 2019;Friedmann Angeli et al, 2014;Li et al, 2019aLi et al, , 2019bLinkermann et al, 2014;Tuo et al, 2017), acute renal failure (Friedmann Angeli et al, 2014), intracerebral hemorrhage (Li et al, 2017), neurodegeneration (Hambright et al, 2017), hemochromatosis (Wang et al, 2017), non-alcoholic steatohepatitis (Qi et al, 2020), and morphine tolerance (Chen et al, 2019), underlining the pathological role of lipid peroxidation and associated ferroptosis in numerous disease contexts. Vitamin E is perhaps the most efficient natural RTA found in organisms (Zilka et al, 2017).…”
Section: Disease Implications and Pharmacological Modulationmentioning
confidence: 99%
“…More importantly, iron levels are regulated by several elements, such as by TFR and FPN1 (Qiu et al., 2020). TFR can recognize iron binding with transferrin and import iron from transferrin into the cells by endocytosis, while FPN1 is the only known iron exporter that can transport iron from the inside to the outside of a cell (Chen et al., 2019; Xu et al., 2019). It was proposed that the imbalance in the levels of TFR and FPN1 may lead to iron accumulation (Qiu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has highlighted the contribution of iron accumulation‐induced ferroptosis in mechanisms underlying diseases of the nervous system (Lewerenz et al., 2018). For example, in the spinal cord, iron accumulation may be correlated with remifentanil‐induced postoperative hyperalgesia and morphine tolerance, and therapies based on the inhibition of iron accumulation and ferroptosis have been demonstrated to be clinically useful in intervening with these neurological symptoms (Chen et al., 2019; Shu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%